2014
DOI: 10.1007/s10067-014-2644-9
|View full text |Cite
|
Sign up to set email alerts
|

An MRI assessment of chronic synovial-based inflammation in gout and its correlation with serum urate levels

Abstract: It is unclear when the synovial-based inflammatory process of gout begins. The aim of this study was to determine the percentage of patients with inter-critical gout who have chronic synovial-based inflammation as evidenced by synovial pannus on a contrast-enhanced magnetic resonance imaging (MRI) of their most involved joint and determine if the presence and/or severity correlates with their serum urate levels. All patients received a 3 T MRI of their index joint, serum urate level, CRP, and creatinine. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Consistent with other imaging studies in patients with gout , MRI detected significantly more erosions and also revealed that most subjects had evidence of synovitis at baseline. A key finding of the current study is that febuxostat treatment led to greater improvements in MRI‐detected synovitis over the 2‐year period compared with placebo treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with other imaging studies in patients with gout , MRI detected significantly more erosions and also revealed that most subjects had evidence of synovitis at baseline. A key finding of the current study is that febuxostat treatment led to greater improvements in MRI‐detected synovitis over the 2‐year period compared with placebo treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Acute 1 st MTP arthritis presenting as the manifestation of gout at disease onset, ranged from 43 to 76 % [ 20 , 32 35 ]. The frequency of acute 1 st MTP arthritis as the initial manifestation of gout was not significantly different between genders [ 34 – 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, their diagnostic performance has been less studied than US and DECT. MRI provides information with regard to the size of tophi, crystal-induced inflammation such as synovitis, and joint damage including bone erosion 86–90. CT can also identify urate deposits but is more efficient in visualising bone damage 91–93.…”
Section: Discussionmentioning
confidence: 99%